The Mechanisms of Space‐Time Association: Comparing Motor and Perceptual Contributions in Time Reproduction. (30th April 2013) - Fabbri, Marco; Cellini, Nicola; Martoni, Monica; Tonetti, Lorenzo; Natale, Vincenzo
Abstract: The spatial‐temporal association indicates that time is represented spatially along a left‐to‐right line. It is unclear whether the spatial‐temporal association is mainly related to a perceptual or a motor component. In addition, the spatial‐temporal association is not consistently found using a time reproduction task. Our rationale for this finding is that, classically, a non‐lateralized button for performing the task has been used. Using two lateralized response buttons, the aim of the study was to find a spatial‐temporal association in a time reproduction task. To account for the perceptual component, reference and target stimuli were presented in different spaces through four experiments. In all experiments, a Spatial‐Temporal Association of Response Codes (STEARC) effect was found and this effect was not modulated by the spatial position of both reference and target stimuli. The results suggested that the spatial‐temporal association was mainly derived from the spatial information provided by response buttons, reflecting a motor but not visuospatial influence.